Epidemiology of Hepatitis C Virus (HCV) Infection - Sultan, Md Tipu; Rahman, Md Mahbubur; Begum, Shahana (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Hepatitis C virus is a significant healthcare problem, affecting more than 170 million people worldwide and as many as 4 million new infections occur annually. Incidence rates across the world fluctuate and are difficult to calculate given the asymptomatic, often latent nature of the disease prior to clinical presentation. Of those exposed to HCV, 80% become chronically infected, and at least 30% of carriers develop chronic liver disease, including cirrhosis and hepatocellular carcinoma. HCV infection also increases the number of complications in persons who are co-infected with HIV. This article reviews an overview of the prevalence, genotype data, transmission risk and prevention. DOI:10.3329/jbcps.v27i3.4294 J Bangladesh Coll Phys Surg 2009; 27: 160-165